2007
DOI: 10.1097/jom.0b013e31802ec6a3
|View full text |Cite
|
Sign up to set email alerts
|

Promising Practices in Employer Health and Productivity Management Efforts: Findings From a Benchmarking Study

Abstract: Increased efforts should be directed at disseminating the experiences of promising practices. However, more research is needed in this area, so that additional public and private funding is made available for applied research in "real-life" business settings. Finally, employers should be provided effective tools and resources to support their HPM efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 30 publications
3
162
1
4
Order By: Relevance
“…There is mounting evidence that work-based wellness offerings are cost-effective (Goetzel and Ozminkowski 2008) and may impact productivity (Goetzel et al 2007). In a period of declining resources for many health care organizations, it is only prudent therefore to introduce and evaluate workplace wellness interventions with implications for employee wellbeing included in the design.…”
Section: Creating a Positive Workplacementioning
confidence: 99%
“…There is mounting evidence that work-based wellness offerings are cost-effective (Goetzel and Ozminkowski 2008) and may impact productivity (Goetzel et al 2007). In a period of declining resources for many health care organizations, it is only prudent therefore to introduce and evaluate workplace wellness interventions with implications for employee wellbeing included in the design.…”
Section: Creating a Positive Workplacementioning
confidence: 99%
“…A 2007 Centers for Disease Control benchmarking study on health and productivity management identified incentives as a key element of encouraging participation. 34 This suggestion has been borne out by research that has shown that incentives can have a significant impact on participation. 17,27,29,35,36 Incentives typically take the form of financial rewards such as discounts on gym memberships or cash payments for participation.…”
Section: Understanding the Relationship Between Incentive Design And mentioning
confidence: 99%
“…23 Indeed, achieving high participation is a key part of guidance on developing effective workplace wellness programs. 6,34 Similarly, employee perceptions of the effectiveness of a program have been identified as drivers of outcomes 50,51 and indicators of the program's fit within the organizational climate. 52 This suggests that there is promise in using employee perceptions of programs as an outcome measure.…”
Section: Is More Always Better When It Comes To Workplace Wellness Prmentioning
confidence: 99%
“…4 Faced with the exponential growth of health costs, many employers are implementing evidence-based health promotion programs, including individual risk reduction programs, connected to environmental support for healthy behaviors, coordinated and integrated into other activities related to wellbeing, which has been shown to be the most efficient strategy to reduce the risk of developing chronic diseases. [5][6][7] Several studies have concluded that health promotion programs in the workplace can improve employee health and reduce the health expenditure of employers. [8][9][10] In North America, 76% of companies have some kind of health promotion program.…”
Section: Introductionmentioning
confidence: 99%